Peningkatan Kompetensi Guru Dalam Meningkatkan Kemampuan Berfikir Dan Bertindak Kreatif Peserta Didik Melalui Pemanfaatan Video Pembelajaran Animasi - Elsa Kristina (Balai Diklat Keagamaan Surabaya, 2022)
This research is motivated by the weakness of teachers in the application of ICT in the learning process in the classroom. This is based on observations in the teacher's lesson plan that never includes ICT-based learning media. The purpose of this study was to determine the increase in teacher competence in applying ICT in the learning process through in-house training. In-house training was chosen as an effort to increase teacher competence because in terms of time it does not interfere with the main task of teachers and in terms of costs it does not require a lot of money, because it is carried out internally in schools. The method used is school action research (PTS) with two cycles, each cycle consisting of planning, implementing corrective actions, observing and reflecting. The results of the study showed that there was an increase in teacher competence in implementing ICT through in-house training for teachers at SDN 3 Sukamenak, Purbaratu District, Tasikmalaya City. Assessment through the in-house training observation rubric in cycle 1 was only 30% ready to take part in the activity, so it was included in the poor category, and the results of the assessment in the second cycle which reached a value of 80%, were in the very good category. While the teacher's activity in the implementation of learning in the second cycle is better than in the first cycle. Where the final result is an increase in teacher competence in applying ICT in the learning process with a 40% increase in the percentage.